New compound proper nouns with rare appellative first stems fromthe Lithuanian Metrica - Sinkevičiūtė, Daiva (Baltistica, 2018)
This article presents 47 new reconstructed compound proper nouns with rare appellative stems from the Lithuanian Metrica. Almost all names are male names and most of them are reconstructed from one of the two members of binary names – either from the name or from the patronymic. For the most part, the whole root of the appellative was used as a member of proper names (cf. bed- (or bėd-), buk- (or būk-), draust-, gruod-, jaun-, kirt-, maist-, malt-, pikt- (or pykt-), skers-, spud- (or spūd-), stir-, šul-, vais-, verš-, žyd-, žied- (or žėd-) and žies- (or žės-)). In other cases, the new member of appellative origin was shortened by losing the last consonant (cf. deg-, dyg- (or dyk-), drug-, duj-, geg-, kiet-, lab- (or lap-), lok- (or log-, liog-, liok-), mag- (or mak-), mut- (or mud-), pišk- (or pyšk-), raug- (or rauk-), reb- (or rep-, rėb-, rėp-, rieb-, riep-), riaub-, rib- (or rip-, ryb-, ryp-), sėd- (or sėt-), staug-, tav-, žav-, žeg- (or žek-, žėg-, žėk-) and žiog- (or žiok-)). This gave rise to new proper name stems beginning with an open syllable. In the second position the usual stems of proper names occur regularly, thus showing that this position was considerably more stable than the first member.